Method for preparing amino-functionalized hollow silicon spheres based on steam condensation method and application of amino-functionalized hollow silicon spheres in adsorption of lead ions
Amino functionalized hollow silicon spheres are prepared in one step by vapor condensation, which solves the problem of complex and unenvironmental preparation process of hollow silicon spheres, and achieves efficient lead ion adsorption performance, which is suitable for efficient removal of lead ions in water.
Patent Information
- Application Number
- CN202411286076.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-13
- Publication Date
- 2024-12-13
AI Technical Summary
In the prior art, the preparation process of hollow silica spheres is complex and not environmentally friendly, making it difficult to achieve controllability of the morphology and structure of silicon spheres, and the efficiency is low in the removal of lead ions in water.
The steam condensation method is used to prepare amino-functional hollow silicon spheres in one step. By regulating the condensation time, surfactant dosage and hydrolysis and condensation rate of silane coupling agent, the hollow structure and morphology of the silicon spheres are controlled, and the amino-functional adsorbent is used to efficiently use Remove lead ions from water.
It realizes low-cost, environmentally friendly silicon sphere preparation, has high specific surface area and excellent lead ion adsorption performance, and is suitable for heavy metal pollution control, simplifies the production process and improves efficiency.
Smart Images

Figure CN119114016A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of preparation of environmentally friendly functional materials, and relates to a new method for preparing functionalized hollow silicon spheres, in particular to a method for preparing amino-functionalized hollow silicon spheres in one step based on a steam condensation method, and its application in heavy metal pollution control Background Art
[0002] Lead is an important industrial heavy metal. Due to its good ductility and plasticity, it is widely used in military industry, shipbuilding equipment and other aspects. At present, the global lead consumption level remains high. At the same time, the mining and use of lead inevitably lead to the pollution of water, atmosphere, soil and food chain, which seriously threatens human life and health. Among them, lead ion pollution in water is particularly serious. Due to the good solubility and fast migration rate of lead ions in aqueous solution, lead ion pollution in water is more persistent and more difficult to control. Therefore, achieving efficient removal of lead ions in water is of great significance to environmental ecology and human life and health. Point solution method, precipitation method, microbial method and adsorption method are commonly used effective means for removing lead ions from water. Among them, the adsorption method is simple to operate and has strong continuity, which has attracted widespread attention from scientific researchers. Realizing the controllable design of the morphology and structure of the adsorbent to achieve efficient lead removal is an important topic in the control of lead ion pollution.
[0003] Compared with traditional spherical adsorbents, hollow silica sphere adsorbents show better specific surface area and higher material utilization efficiency, which has aroused research interest in the field of adsorption separation. However, the preparation of hollow silica spheres is still limited by the hard template method, which is complicated and not environmentally friendly. The reported method of preparing hollow silica spheres based on the emulsion template method is difficult to control the hollow structure and the morphology and size of the silica spheres. Summary of the invention
[0004] As an efficient low-energy emulsification technology, the steam condensation method is widely used in the controllable preparation of nanoemulsions. By flexibly adjusting various process parameters, it can achieve precise control of the droplet size, showing excellent versatility and controllability. In addition, the steam condensation method is also a continuous preparation platform. The preparation of amino-functionalized silica spheres based on the steam condensation method can not only achieve the control of their particle size and structural morphology, but also achieve continuous preparation and large-scale production.
[0005] SUMMARY OF THE INVENTION In view of the problems existing in the prior art, the present invention first prepares an oil-in-water type nanoemulsion by a steam condensation method, and uses a silane coupling agent dissolved in an oil phase to undergo a hydrolysis condensation reaction at an oil-water interface under an alkaline catalytic environment to prepare amino-functionalized hollow silicon spheres. This method provides a production platform for the continuous preparation of silicon spheres, and can achieve a one-step preparation of amino-functionalized hollow silicon spheres. In addition, by regulating various parameters and combining the hydrolysis condensation rate of the silicon sphere coupling agent, the growth of silicon dioxide can be restricted to the droplet interface, and the hollow structure of the silicon sphere can be regulated and the spherical morphology can be optimized. Subsequently, the amino-functional adsorbent is used to remove lead ions in an aqueous solution, and rapid and efficient adsorption is achieved.
[0006] The present invention solves the problems of high preparation cost, complicated process and difficulty in large-scale production of amino-functionalized silicon spheres. A steam condensation method is adopted to prepare a nano droplet reactor, the size of the droplets is regulated by adjusting the condensation time and the amount of surfactant used, and the spherical morphology and hollow structure are regulated by adjusting the amount of silane coupling agent used. Subsequently, based on the coordination effect between amino groups and lead ions, efficient removal of lead ions in the aqueous solution is achieved.
[0007] A method for preparing amino-functionalized hollow silicon spheres based on a steam condensation method comprises the following steps:
[0008] (1) Dissolve surfactant, tetraethyl orthosilicate (TEOS) and 3-aminopropyltriethoxysilane (APTS) in oil phase n-dodecane according to proportion, and then transfer to a glass watch glass;
[0009] (2) using a humidifier and a constant temperature and humidity chamber to control the humidity of the enclosed space to between 75% and 80% and the temperature to 25° C., placing a watch glass in the enclosed space and controlling the temperature of the watch glass to between 0° C. and 3° C. using an ice water bath; using water vapor in the air to condense on the surface of the oil phase for a period of time;
[0010] (3) After the condensation is completed, the watch dish is sealed and placed in a constant temperature environment for reaction to prepare amino-functionalized hollow silica spheres.
[0011] In step (1), the surfactant is Span 80, and the usage ratio of Span 80, TEOS, APTS and n-dodecane is (0.1-0.5) g: (0.15-0.6) mL: (0.05-0.25) mL: (5-15) mL.
[0012] In step (2), the humidity of the enclosed space is between 75% and 80%, the temperature of the enclosed space is 25° C., and the condensation time is 15 to 40 minutes.
[0013] In step (3), the constant temperature environment is 25-60° C. and the reaction time is 1.0-7.0 h.
[0014] The amino-functionalized hollow silica spheres prepared by the steam condensation method of the present invention are used for adsorbing and removing lead ions in an aqueous solution.
[0015] Compared with the prior art, the beneficial effects of the present invention are embodied in the following aspects:
[0016] The present invention uses a steam condensation method to prepare nanoemulsions and nanodroplets with adjustable particle size as the reaction site. It uses a completely new method to prepare amino-functionalized hollow silica spheres in one step and use them to remove lead ions from water. The method for preparing amino-functionalized hollow silica spheres has the following advantages:
[0017] In this work, the steam condensation method was used to prepare nanoemulsions. This method is a continuous low-energy emulsification method that can not only realize the large-scale preparation of oil-in-water nanoemulsions, but also has low equipment requirements, simple operation, and a concise process. It can achieve size control of nanodroplets and is a good platform for the preparation of nanomaterials.
[0018] The present invention uses oil-in-water nanoemulsion as a template to achieve a one-step preparation of amino-functionalized hollow silica spheres. Compared with the traditional hard template method, it effectively solves the problem of high cost caused by template etching and avoids the post-modification process and deformation caused by post-modification.
[0019] The present invention uses the alkaline catalytic environment created by APTS to catalyze the growth of silicon dioxide, and at the same time, APTS itself also participates in the growth of hollow silicon spheres as a functionalized silane coupling agent to achieve surface amino functionalization, thereby avoiding the adverse effects of strong acids and strong bases introduced due to catalysis on the environment.
[0020] The method for preparing functionalized amino hollow silica spheres is controllable and can achieve regulation of their size, regulation of the hollow structure and regulation of the hollow wall thickness.
[0021] The amino-functionalized hollow silica sphere adsorbent prepared by the present invention has a large specific surface area, can effectively improve the adsorption capacity, and enhance its adsorption performance for lead ions, and has good application potential in the treatment of heavy metal pollutants. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 It is the droplet particle size distribution diagram of the nanoemulsions 1-10, 1-20, 1-30, 2-10, 2-20, 2-30 and 3-10, 3-20, 3-30 prepared in Comparative Example 1.
[0023] Figure 2These are SEM images of SN1-10, SN1-20, SN1-30 and SN2-10, SN2-20, SN2-30 and SN3-10, SN3-20, SN3-30 prepared at different amounts of Span 80 in Comparative Example 2, Example 1 and Example 2.
[0024] Figure 3 These are the SEM images (ad) and TEM (a1-d1) of SN3-2, SN3-3, SN3-4, and SN3-5 prepared in Example 3.
[0025] Figure 4 These are the SEM images (ad) of SN1-2, SN1-3, SN1-4, and SN1-5 prepared in Example 4 and the TEM images (e, f) of SN1-5.
[0026] Figure 5 It is the infrared absorption spectra of SN3-2, SN3-3, SN3-5 prepared in Example 3, SN1-5 of Example 4, and SN3-2-Pb, SN3-3-Pb, SN3-5-Pb, and SN1-5-Pb after adsorbing lead ions.
[0027] Figure 6 The effect of different initial pH environments on the lead ion adsorption capacity of SN3-2, SN3-3, SN3-5 and SN1-5.
[0028] Figure 7 The adsorption capacity of lead ions of SN3-2, SN3-3, SN3-5 and SN1-5 at different adsorption times and the pseudo-first-order and pseudo-second-order kinetic fitting curves.
[0029] Figure 8 The adsorption capacities of SN3-2, SN3-3, SN3-5 and SN1-5 at different initial lead ion concentrations and their Langmuir and Freundlich model fitting curves.
[0030] Fig. 9 This is the XPS analysis spectrum of SN3-2-Pb before and after SN3-2 adsorbs lead ions. DETAILED DESCRIPTION
[0031] Comparative Example 1
[0032] Preparation of Nanoemulsion by Vapor Condensation Method
[0033] Span 80 (0.107 g) was mixed with 10 mL of n-dodecane as the oil phase and placed in a glass culture dish. Subsequently, the oil phase was placed in a constant temperature and humidity chamber with a humidity of 75%-80%, and its temperature was controlled to be stable in the range of 0-3°C with an ice water bath, and was allowed to stand for 10 min, 20 min and 30 min, respectively, and the ambient temperature was controlled to be 25°C, to obtain nanoemulsions with different condensation times, which were recorded as 1-10, 1-20 and 1-30, respectively.
[0034] Under the same conditions, when the amount of Span 80 was 0.2143 g, the condensation time was 10 min, 20 min, and 30 min, respectively, and the obtained emulsions were recorded as 2-10, 2-20, and 2-30;
[0035] Under the same conditions, when the amount of Span 80 was 0.4286 g, the condensation time was 10 min, 20 min and 30 min, respectively, and the obtained emulsions were recorded as 3-10, 3-20, and 3-30, respectively.
[0036] like Figure 1 In the figure, there are droplet size distribution diagrams of different emulsions. It shows that increasing the amount of Span 80 can reduce the droplet size of the nanoemulsion prepared by the steam condensation method, and prolonging the condensation time will increase the droplet size. When the amount of Span 80 increases to 0.4286g, the effect of condensation time on the emulsion droplet size becomes smaller.
[0037] Comparative Example 2
[0038] 0.107 g, 0.2143 g and 0.4286 g of Span 80 were respectively completely mixed with 10 mL of n-dodecane, and 0.3 mL of LTEOS and 0.2 mL of APTS were added. The mixture was evenly mixed by ultrasonication and placed in a high humidity and closed environment. The humidity was controlled to be 75%-80% and the ambient temperature was 25°C. The oil phase temperature was controlled to be 0-3°C in an ice water bath. The mixture was allowed to stand for condensation for 10 min, and the watch dish was sealed and placed in a constant temperature oven at 40°C. The white products were allowed to stand for 6.0 h and then centrifuged to obtain the white products, which were respectively recorded as SN1-10, SN2-10 and SN3-10.
[0039] like Figure 2 As shown, when the condensation time was controlled to 10 min, spherical silicon balls were obtained without showing obvious hollow structures.
[0040] Example 1
[0041] 0.107 g, 0.2143 g and 0.4286 g of Span 80 were respectively mixed with 10 mL of n-dodecane, and 0.3 mL of LTEOS and 0.2 mL of APTS were added to each of them. The mixture was evenly mixed by ultrasonication and placed in a high humidity and closed environment. The humidity was controlled to be 75%-80% and the ambient temperature was 25°C. The oil phase temperature was controlled to be 0-3°C in an ice water bath. The mixture was allowed to stand for condensation for 20 minutes. The watch dish was sealed and placed in a constant temperature oven at 40°C. The mixture was allowed to stand for 6.0 hours and then centrifuged to obtain white products, which were recorded as SN1-20, SN2-20 and SN3-20.
[0042] like Figure 2 As shown, when the condensation time is 20 minutes, amino-functionalized silica spheres with collapsed shells can be obtained, indicating that complete amino-functionalized hollow silica spheres can be formed when the condensation time is 20 minutes.
[0043] Example 2
[0044] 0.107 g, 0.2143 g and 0.4286 g of Span 80 were mixed with 10 mL of n-dodecane, and 0.3 mL of LTEOS and 0.2 mL of APTS were added to the mixture. The mixture was uniformly mixed by ultrasonication and placed in a high humidity and closed environment. The humidity was controlled to be 75%-80% and the ambient temperature was 25°C. The oil phase temperature was controlled to be 0-3°C in an ice-water bath. The mixture was allowed to stand for condensation for 30 minutes. The watch dish was sealed and placed in a constant temperature oven at 40°C. The mixture was allowed to stand for 6.0 hours and then centrifuged to obtain white products, which were recorded as SN1-30, SN2-30 and SN3-30.
[0045] like Figure 2 As shown, the collapse of the shell layer of the amino-functionalized silica sphere reveals its hollow structure, among which SN3-30 presents a hollow hemisphere structure.
[0046] Example 3
[0047] 0.4286g Span 80 and 0.1mL APTS were dissolved in 10mL n-dodecane, followed by adding 0.2mL, 0.3mL, 0.4mL and 0.5mL TEOS, respectively, and placed in a 25°C constant temperature and humidity chamber, with the humidity set to 75%-80%, and an ice-water bath to control the temperature of the oil phase to 0-3°C. After condensation for 20 minutes, the culture dish was taken out, sealed and placed in an oven at 40°C. After standing for 6 hours, the white product was obtained by centrifugation, and SN3-2, SN3-3, SN3-4 and SN3-5 were obtained, respectively.
[0048] like Figure 3In the figure, the SEM and TEM images of SN3-2, SN3-3, SN3-4 and SN3-5 are shown respectively. The silicon spheres gradually grow from collapsed irregular morphology to regular hollow spherical structures, indicating that the addition of TEOS can improve the morphology of amino-functionalized hollow silicon spheres and increase the wall thickness of the hollow silicon spheres.
[0049] Example 4
[0050] 0.107g Span 80 and 0.1mL APTS were dissolved in 10mL n-dodecane, followed by adding 0.2mL, 0.3mL, 0.4mL and 0.5mL TEOS, respectively, and placed in a 25°C constant temperature and humidity chamber, with the humidity set to 75%-80%, and an ice-water bath to control the temperature of the oil phase to 0-3°C. After condensation for 20 minutes, the culture dish was taken out, sealed and placed in an oven at 40°C. After standing for 6 hours, the white product was obtained by centrifugation, and SN1-2, SN1-3, SN1-4 and SN1-5 were obtained, respectively.
[0051] like Figure 4 In the figure, the SEM images of SN1-2, SN1-3, SN1-4 and SN1-5, as well as the SEM magnified image and TEM image of SN1-5 are shown. The amino-functionalized silicon spheres form a hollow hemispherical structure due to the rupture of the shell layer.
[0052] like Figure 5 As shown, the infrared absorption spectra of SN3-2, SN3-3, SN3-5 prepared in Example 3 and SN1-5 prepared in Example 4, and the infrared absorption spectra of SN3-2-Pb, SN3-3-Pb, SN3-5-Pb, and SN1-5-Pb after adsorbing lead ions are shown. It is shown that the surfaces of the four amino-functionalized hollow silica spheres have amino functional groups, and the infrared absorption peaks of the amino groups shift before and after adsorbing lead ions, indicating that the amino functional group is the key to adsorbing lead ions.
[0053] Example 5
[0054] Accurately weigh 1.0 mg of SN3-2, SN3-3, SN3-5 prepared in Example 3 and SN1-5 prepared in Example 4 into a centrifuge tube, and add 4.0 mL of Pb with pH values of 3.0, 4.0, 5.0 and 6.0, respectively. 2+ The solution (100 mg / L) was placed in a 25°C water bath oscillator and centrifuged after 3.0 h to obtain the supernatant for the detection of residual Pb 2+ Each group of experiments was performed in triplicate.
[0055] like Figure 6As shown, the adsorption amount of lead ions by SN3-2, SN3-3, SN3-5 prepared in Example 3 and SN1-5 prepared in Example 4 under different pH environments. It is shown that the adsorption capacity of the four adsorbents is optimal when the pH is 5 and 6.
[0056] Example 6
[0057] Take 4.0mL Pb 2+ The solution (100 mg / L) was transferred into a centrifuge tube, and 1.0 mg of adsorbent (SN3-2, SN3-3, SN3-5 or SN1-5) was added. The static adsorption time was 1.0 min, 5.0 min, 10 min, 20 min, 40 min, 80 min and 160 min, respectively. The supernatant was taken by centrifugation and the adsorption capacity at different adsorption times was determined. Three parallel experiments were performed for each group of experiments.
[0058] like Figure 7 As shown, the adsorption capacity of lead ions of SN3-2, SN3-3, SN3-5 prepared in Example 3 and SN1-5 prepared in Example 4 at different adsorption times, as well as the kinetic fitting of related data. All four materials conform to the pseudo-second-order kinetic model. It shows that the adsorption capacity of the four adsorbents rises rapidly within 20 minutes, then grows slowly, and finally reaches adsorption equilibrium at about 80 minutes.
[0059] Example 7
[0060] Accurately weigh five groups of 1.0 mg of the adsorbent prepared in Example 3 (SN3-2, SN3-3, SN3-5 or SN1-5) into a centrifuge tube, and add 4.0 mL of Pb 2+ The solutions were placed in a 25°C water bath shaker with concentrations of 150 mg / L, 200 mg / L, 300 mg / L, 400 mg / L and 500 mg / L. After 3.0 h, the supernatant was centrifuged and tested for residual Pb. 2+ Each group of experiments was performed in triplicate.
[0061] like Figure 8 As shown, the adsorption capacities of SN3-2, SN3-3, SN3-5 prepared in Example 3 and SN1-5 prepared in Example 4 at different initial lead ion concentrations are shown. It is shown that the adsorption process of the four adsorbents is more consistent with the Langmuir model, indicating that the adsorption process is a monolayer adsorption on the surface of the adsorbent. The maximum adsorption capacities of SN3-2, SN3-3, SN3-5 and SN1-5 calculated by model fitting are 567.0 mg / g, 508.2 mg / g, 465.6 mg / g and 546.7 mg / g, respectively.
[0062] Fig. 9 This is the XPS analysis spectrum of SN3-2-Pb before and after SN3-2 adsorbs lead ions in Example 7. 2+ Before and after, the binding energy of O1s and N1s shifted significantly (>0.4 eV), and the amino functional groups on the surface of SN3-2 and Pb 2+ The strong complexation between them is the key to achieve efficient adsorption of Pb 2+ The key.
Claims
1. A method for preparing amino-functionalized hollow silicon spheres based on steam condensation method, It is characterized in that The steps include: (1) dissolving surfactant, tetraethyl orthosilicate (TEOS) and 3-aminopropyltriethoxysilane (APTS) in oil phase n-dodecane in proportion, and then transferring to a glass watch glass; (2) using a humidifier and a constant temperature and humidity chamber to control the humidity and temperature of the enclosed space, placing a watch glass in the enclosed space, and using an ice water bath to control the temperature of the watch glass to be between 0 and 3° C.; using water vapor in the air to condense on the surface of the oil phase for a period of time; (3) After the condensation is completed, the watch dish is sealed and placed in a constant temperature environment for reaction to prepare amino-functionalized hollow silica spheres.
2. The method for preparing amino-functionalized hollow silicon spheres based on the steam condensation method according to claim 1, It is characterized in that In step (1), the surfactant is Span 80, and the usage ratio of Span 80, TEOS, APTS and n-dodecane is (0.1-0.5) g: (0.15-0.6) mL: (0.05-0.25) mL: (5-15) mL.
3. The method for preparing amino-functionalized hollow silicon spheres based on steam condensation method according to claim 1, It is characterized in that In step (2), the humidity of the enclosed space is between 75% and 80%, and the temperature of the enclosed space is 25°C.
4. The method for preparing amino-functionalized hollow silicon spheres based on steam condensation method according to claim 1, It is characterized in that In step (2), the condensation time is 15-40 minutes.
5. The method for preparing amino-functionalized hollow silicon spheres based on steam condensation method according to claim 1, It is characterized in that In step (3), the temperature of the constant temperature environment is 25-60° C., and the reaction time is 1.0-7.0 h.
6. Use of the amino-functionalized hollow silica spheres prepared by the steam condensation method according to any one of claims 1 to 5 for adsorbing and removing lead ions from an aqueous solution.
